Features of the Initiative of Modern Preschoolers - Smirnova E.O.; Soldatova Y.S. (Психолого-педагогические исследования, 2019)
The article discusses children's initiative as the most important prerequisite for creativity. A study of the forms of manifestation of initiative of preschool children in an open, uncertain situation is presented. The study involved 50 children aged 5—7 years from two kindergartens in Moscow. The observation of the free activity of children in a specially organized open space was used as a research method. This spase was providing opportunities for various types of children's activities. It turned out that in a free situation, children tend to choose socially acceptable and familiar activities, such as drawing. The free play almost does not occur without the participation of an adult. Based on the results obtained, it is concluded that the predominant form of initiative is productive, which is the most “cultivated” in preschool education. The findings suggest the need to create special conditions for the development of initiative of preschoolers. Special attention should be paid to the organization of conditions to support children's creative initiative.